Flow immunophenotyping of benign lymph nodes sampled by FNA: Representative with diagnostic pitfalls. Issue 9 (7th September 2018) - Scott, Gregory D.; Lau, Hubert D.; Kurzer, Jason H.; Kong, Christina S.; Gratzinger, Dita A.
Abstract : Background: Fine‐needle aspiration with flow cytometry (FNA‐FC) is routinely used in the evaluation of lymph nodes suspicious for lymphoma, yet data comparing immunophenotype distributions and outliers in benign lymph nodes sampled by fine‐needle aspiration (FNA) versus excision are lacking. Methods: Flow cytometry data from 289 benign lymph node FNA cases were assessed for the overall antigen distribution, with a focus on outliers relevant to the diagnosis of lymphoma. Distributions and outlier proportions were compared with those of a separate cohort of 298 excisional biopsies. Results: Compared with excisional biopsies, FNA specimens overrepresented CD3+ events (72% vs 63%), underrepresented CD19+ events (22% vs 29%), and had 25% fewer large cell–gated events. Normalized antigen distributions in FNA were equivalent to those in excisional biopsy. Twenty‐three percent of FNA‐FC cases exhibited an outlier, including a skewed kappa:lambda light‐chain ratio, increased CD5+ or CD10+ B‐cell events, a skewed CD4:CD8 ratio, and increased CD7 loss on T cells, with no significant differences in frequency or type in comparison with excisional specimens. Outliers for the light‐chain ratio and T‐cell antigens were enriched among older patients and included patients with a variety of autoimmune/rheumatologic conditions. Conclusions: Benign lymph node FNA yields flow immunophenotypes remarkably similar to those from excisional biopsies. Outlier flow immunophenotypes are identified in benign lymph nodes sampled by FNA at a frequency similar to that with excisional biopsies. Older patients, who have a higher baseline risk of lymphoma, are more likely to exhibit lymphoma‐mimicking outliers such as a light‐chain predominance on B cells and skewed CD4:CD8 ratios or increased CD7 loss on T cells, and they warrant additional diagnostic caution. Abstract : Fine‐needle aspiration–based flow cytometry of lymph nodes is comparable to excisional biopsy and exhibits similar outliers. The reference ranges provided in this study can aid pathologists and contribute in the long term to computational flow analysis and biomedical research.